Nighttime Temperatures and Sunlight Intensities Interact to Influence Anthocyanin Biosynthesis and Photooxidative Sunburn in “Fuji” Apple - Xue, Xiaomin; Duan, Ying; Wang, Jinzheng; Ma, Fengwang; Li, Pengmin (Frontiers in Plant Science, 2021)
Light and low temperatures induce anthocyanin accumulation, but intense sunlight causes photooxidative sunburn. Nonetheless, there have been few studies of anthocyanin synthesis under different sunlight intensities and low nighttime temperatures. Here, low nighttime temperatures followed by low light intensity were associated with greater anthocyanin accumulation and expression of anthocyanin biosynthesis genes in ‘Fuji’ apple peel. UDP-glucose flavonoid-3-O-glucosyltransferase (UFGT) activity was positively associated with anthocyanin enrichment. Exogenous ascorbate altered anthocyanin accumulation and reduced the occurrence of high light–induced photooxidative sunburn by removing hydrogen peroxide from the peel. Overall, low light intensity was beneficial for anthocyanin accumulation and did not cause photooxidative sunburn, whereas natural light had the opposite effect on apple peel at low nighttime temperatures. This study provides insight into the mechanisms by which low temperatures induce apple coloration and high light intensity cause photooxidative sunburn.